Use of Endoscopic Ultrasound in Diagnosing Plasmacytoma of the Pancreas - Miljkovic’, Milos; Senadhi, Viplove (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Context An extramedullary plasmacytoma is a discrete collection of monoclonal plasmocytes arising in tissues other than the bone. Gastrointestinal<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">involvement<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">has<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">been<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">reported<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">in<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">approximately<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">10%<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">cases<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">and<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">usually<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">involves<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">liver; however, there have been a number of cases involving the pancreas. <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Discussion Although helical CT can be used to diagnose pancreatic plasmacytomas based on a typical radiological appearance, there are a number of pitfalls with CT including similar radiologic appearances of other pancreatic tumors, malignant seeding induced by CT biopsy, and creation of multiple secondary plasmacytomas precipitated by CT biopsy. Tissue<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">diagnosis<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">is<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">critical<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">to<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">management<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">in<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">pancreatic<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">lesions<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">as<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">decision<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">to<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">pursue<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">surgery<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">(pancreatic<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">adenocarcinoma)<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">versus<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">chemotherapy<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">(lymphoma)<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">or<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">radiation<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">(extramedullary plasmacytoma)<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">is<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">dependent<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">on<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">a<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">correct<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">tissue<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">diagnosis.<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Tissue<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">diagnosis<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">can<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">change<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">morbidity<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">and<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">mortality<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">with<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">respect<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">to<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">specific<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">treatment<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">pancreatic<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">lesions<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">in<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">milieu<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">pancreatic<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">tumor<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">variance. In the confirmed tissue<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">diagnosis<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">pancreatic<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">plasmacytoma,<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">radiation<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">and<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">chemotherapy<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">can<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">be<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">preferentially<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">chosen<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">over<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">high<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">risk<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">surgery. EUS-FNA has a lower risk of malignant seeding, complications, and a high sensitivity in the diagnosis of pancreatic plasmacytomas, especially with an increased number of passes and bedside cytopathologists. <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: SimSun; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Conclusion It is important for physicians to have a high index of suspicion for diagnosing pancreatic plasmacytomas in the appropriate clinical setting (i.e., a previously diagnosed multiple myeloma, extramedullary plasmacytoma or any other plasma cell neoplasm). EUS-FNA is now an indispensable imaging modality to achieve the diagnosis of pancreatic extramedullary plasmacytomas with an inherently lower rate of complications, and should be the first choice for tissue evaluation.